KARAKTERISTIK KIMIAWI TEPUNG MOCAF DENGAN VARIASI FERMENTASI SPONTAN MENGGUNAKAN YOUGHURT SEBAGAI STARTER CULTURE - Akhmad Mustofa, Y. Wuri Wulandari & (JITIPARI, 2016)
Mocaf or modified cassava flour is a cassava flour that is specifically processed by modifying of cassavacells though fermentation. The aim of the research was to produce mocaf by fermentation with differenttreatment, thera are by spontaneous fermentation and by species youghurt as bacteria culture.The research showed that treatment of fermentation would influence the characteristic of cassavaflour. Flour taste was unidentified and didn?t have cassava odor. Treatment fermentation by youghurt wasproduced higher quality cassava flour with specific characteristic are moisture content (11,957%), amilumcontent (79,934%), protein content (0,935%), lipid content (4,650%), ash content (0,321%), celulose content(1,795%), kalsium content (0,321 mg/100g), Fe content (54,041 mg/100g), fosfor content (178,596 mg/100 g),and HCN content HCN (23.751 ppm)Keywords: mocaf, flour, and cassava